Sociala medier och den skimrande dialogen - ett kritiskt perspektiv på ett sjukhus Facebooksida - Blohmé,Jessica; Olsson,Clara (2019)
By examining Skåne University Hospital, hereafter Sus, Facebook page this study aims to increase the understanding of the communicative choice of being present on social media. This study aims to contribute with knowledge about, and how, communication and activities on social media can contribute to the strategic communication and goals of an authority. The problem formulation of this study consists of the knowledge gap we identified in the literature regarding why authorities should be on social media. Our empirical data consists of Region Skåne's steering documents, Sus's communication and organizational goals, posts and interactions on Sus's Facebook page and statements from an interview with an employee at Sus's editorial team. As data collection methods we have used netnography and interview, afterwards we conducted a quantitative content analysis and a qualitative discourse analysis. Thus, we have used both a quantitative and a qualitative approach. In the analysis, the empirics are contextualized based on both theories and concepts derived from the field of strategic communication and on societal theories such as New Public Management, hereafter NPM, and isomorphism. The analysis shows that the use of social media in health care organizations is a result of NPM and is explained by isomorphism and translation theory. We saw indications that a citizen logic has been replaced by a service logic where dialogue and interaction are seen as desirable but in practice is difficult to achieve. We have tried to define what type of dialogue that takes place on Sus Facebook page and further problematized the concept of dialogue. We have identified a lack of communication planning by analyzing their presence on Facebook in relation to the steering documents Sus follows. Thereby we discovered a discrepancy between what they want to achieve and what actually takes place on their Facebook page. We came to the conclusion that Facebook is currently not contributing to Sus's goals or their strategic communication. Changes in the goal formulation have to be made and a clearer communication planning should be implemented to reach more people. The study aims to contribute to the research field strategic communication.
Keywords: Strategisk kommunikation; NPM; dialog; sociala medier; isomorfism; Facebook; medieval; sjukvård; patientkommunikation; social mediediskurs; Strategic communication; dialogue; social media; isomorphism; choice of media; health care; communication; discourse